Zerumbone reduces TLR2 stimulation-induced M1 macrophage polarization pattern via upregulation of Nrf-2 expression in murine macrophages - Marwa Qadri; Zenat Khired; Reem Alaqi; Sandy Elsayed; Abdulaziz Alarifi; Rayan Ahmed; Hussain Alhamami; Amani Khardali; Walaa Hakami (Elsevier, 2024)
Hyperuricemia contributes significantly to gout arthritis pathogenesis, which promotes urate crystal deposition in the joints and activates joint-resident macrophages and circulating monocytes to initiate a state of inflammatory arthritis. In the joint, macrophages have an immune defense role where the presence of urate crystals results in the inflammatory mediators secretion, inflammatory cells recruitment to the joint, and shift macrophage population toward M1 pro-inflammatory phenotypes. Current treatment modalities of gout arthritis have side effects that limit their use in the elderly. A novel treatment that targets macrophage polarization to re-establish homeostasis may initiate a drug discovery program of novel disease-modifying agents for gout. Zerumbone (Zer) is a sesquiterpenoid bioactive compound found in the rhizome of Zingiberaceae family and possesses anti-inflammatory, antioxidant, and anti-proliferative activity. Our study hypothesized that soluble uric acid (sUA) and Pam3CSK4 (TLR2 agonist) reduce the anti-inflammatory function of murine M2 bone marrow-derived macrophages and change the expression of M2 genetic markers toward M1 phenotypes. We observed that priming of M2 macrophages with sUA and Pam3CSK4 significantly decreased M2 specific markers expression, e.g., Arg-1, Ym-1, and Fizz-1, enhanced mRNA expression of IL-1β, TNF-α, CXCL2, and iNOS and increased oxidative stress in M2 macrophages, as exhibited by a reduction in Nrf2 expression. We also aimed to study the impact of Zer on reducing the pro-inflammatory effect of sUA in TLR2-stimulated M2 macrophages. We noticed that Zer treatment significantly reduced L-1β and TNF-α production following Pam3CSK4 + sUA treatment on M2 macrophages. Furthermore, Zer reduced the caspase-1 activity without altering cytosolic NLRP3 content in challenged M2 BMDMs. We also observed that Zer significantly enhanced M2-associated marker's expression, e.g., Arg-1, Ym-1, and Fizz-1, and augmented Nrf-2 and other antioxidant proteins, including HMOX1 and srxn1expression following Pam3CSK4 + sUA treatment. We draw the conclusion that Zer is a potentially effective anti-inflammatory treatment for gout arthritis linked to hyperuricemia.